Acute Transfusion-Associated Lung Injury - A. N. Afonin; V. V. Moroz; N. A. Karpun (Общая реаниматология)
The material of this publication has been prepared, by reviewing the data available in the Russian and foreign literatures on acute transfusion-associated lung injury. The paper considers the history of its study and the state-of-the-art. The epidemiology, etiology, pathogenesis, and pathomorphology of this complication are discussed. Particular emphasis is laid on the diagnosis of acute transfusion-associated lung injury, on the current criteria for verification of its diagnosis, and on the principles of a differentially diagnostic search. The clinical picture and treatment of this pathology are considered. The conclusion of the review gives the recommendations made by Russian and foreign experts to prevent acute transfusion-associated lung injury. Key words: acute transfusion-associated lung injury.